Crystal-to-crystal transformation amongst dimorphs of racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates that achieves halogen bonding contacts - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2008)
{Racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates (bromo (1) and chloro (2)) produced two polymorphs each, thin needle type crystals (Form I) were obtained from methanol, whereas larger rectangular crystals (Form II) were produced from ethyl acetate. Both forms could be produced concomitantly on crystallization (of 1 or 2) from ethyl acetate-light petroleum ether mixture; the yield of Form II crystal was always much more compared to Form I crystals. Although, a one-dimensional isostucturality linking molecules via O-H center dot center dot center dot O hydrogen bonding is seen in both forms, the difference arises in linking these chains. In larger Form II crystals (of 1 and 2), the adhesions are via halogen bonding (C-X center dot center dot center dot O=C